Determination of the De Novo Minimum Selection Concentration of Trimethoprim In Vivo for Escherichia coli Using Galleria mellonella: A Pilot Study - Jaime Knox Macleod; Zina Gestels; Said Abdellati; Thibaut Vanbaelen; Chris Kenyon; Sheeba Santhini Manoharan-Basil (Microorganisms)
We investigated whether the maximum residual levels of trimethoprim permitted in food (Acceptable Daily Intake—ADI) could select for de novo trimethoprim resistance in Escherichia coli in vivo. We designed chronic infection models of E. coli in Galleria mellonella and exposed them to sub-ADI doses of trimethoprim through a single-dosing regimen. The emergence of trimethoprim resistance was determined by isolating the target bacteria on selective agar plates, followed by species confirmation using MALDI-TOF mass spectrometry. The minimum inhibitory concentration (MIC) was assessed via the E-test to determine E. coli susceptibility to trimethoprim. Notably, exposure to as low as one-tenth of the ADI dose through a single-dosing regimen resulted in the selection of trimethoprim-resistant E. coli. Our findings indicate that trimethoprim doses ten-fold lower than the established ADI threshold could induce resistance to trimethoprim in E. coli. These results highlight the importance of considering antimicrobial resistance induction as a key factor when determining ADI levels in food.